Cable-Driven Parallel Robots Proceedings of the Third International Conference on Cable-Driven Parallel Robots - Gosselin, Clément; Cardou, Philippe; Bruckmann, Tobias; Pott, Andreas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents proceedings of the third international conference in this field, continuing the success of the previous events. The peer-reviewed and the selected papers are arranged to make the proposed book the most recent and complete overview on the State-of-the-Art in Cable-Driven Parallel Robots! The conference took place 2017 in Quebec, QC, Canada,.
Modelling of Flexible Cable-Driven Parallel Robots using a Rayleigh-Ritz Approach -- Assumed-mode-based Dynamic Model for Cable Robots with Non-straight Cables -- Manipulator Deflection for Optimum Tension of Cable-Driven Robots with Parameter Variations -- Sensitivity Analysis of the Elasto-Geometrical Model of Cable-Driven Parallel Robots -- CASPR-ROS: A Generalised Cable Robot Software in ROS for Hardware -- A Polymer Cable Creep Modeling for a Cable-Driven Parallel Robot in a Heavy Payload Application -- Bending Fatigue Strength and Lifetime of Fiber Ropes.
Keywords: Control engineering; Robotics; Automation; Artificial intelligence; Machinery; Multibody systems; Vibration; Mechanics, Applied; Control, Robotics, Automation; Artificial Intelligence; Machinery and Machine Elements; Multibody Systems and Mechanical Vibrations; Control and Systems Theory